2018
DOI: 10.1007/s12011-018-1355-5
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, Lead, Cadmium, and Barium Levels in Human Breast Milk and Factors Affecting Their Concentrations in Hamadan, Iran

Abstract: Breast milk is considered the best source of nutrition for all infants. However, exposure of newborns to toxic metals is of special interest due to their potential harmful effects. Thus, the primary aims of this study were to determine the concentration of toxic heavy metals including lead, mercury, cadmium, and barium in breast milk samples from Hamadan, Iran, in relation to some sociodemographic variables. A total of 100 breast milk samples were collected and their heavy metal contents were measured by induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…Recently, two cross-sectional studies conducted in Iran detected high Pb levels in HM. Gasoline, food, water, dust, and cosmetics (lipstick) were identified as possible contamination sources ( Khanjani et al, 2018 ; Vahidinia et al, 2019 ). However, the present study found a mean Pb concentration in HM-baseline similar to another Brazilian study ( Marques et al, 2013 ), and the values were within acceptable WHO limits ( WHO/IAEA, 1989 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two cross-sectional studies conducted in Iran detected high Pb levels in HM. Gasoline, food, water, dust, and cosmetics (lipstick) were identified as possible contamination sources ( Khanjani et al, 2018 ; Vahidinia et al, 2019 ). However, the present study found a mean Pb concentration in HM-baseline similar to another Brazilian study ( Marques et al, 2013 ), and the values were within acceptable WHO limits ( WHO/IAEA, 1989 ).…”
Section: Resultsmentioning
confidence: 99%
“…A multicenter WHO study identified that the normal range for Hg concentration in HM is 1.4–3.3 μg/L ( WHO/IAEA, 1989 ). Moreover, recent studies have shown that breast milk Hg levels range from 0.5 to 7.0 μg/L worldwide ( Cunha et al, 2013 ; García-Esquinas et al, 2011 ; Rebelo and Caldas, 2016 ; Vahidinia et al, 2019 ). Although some studies have reported a positive correlation between fish consumption and Hg accumulation in breast milk, a recent cross-sectional study showed no association between these factors ( Behrooz et al, 2012 ; Letinić et al, 2016 ; Vahidinia et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have proposed the existence of lactational programming [62]. In almost all of them, the effects of pollutants on breast milk composition focused on the ingestion of chemicals such as organochlorine pesticides, bisphenol A, dioxins or heavy metals [46, 53, 6365]. Few data are available on airway pollution or fine particle inhalation, except in the context of passive smoking [54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, people are continuously at risk of exposure to lead. Previous studies have assessed lead levels in blood, plasma, breast milk, saliva, and other biological samples [ 7 , 11 13 ]. A systematic review of studies conducted in Iran showed that the vast majority of breast milk samples contained lead levels above the World Health Organization’s recommended level (< 5 μg/L) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have assessed lead levels in blood, plasma, breast milk, saliva, and other biological samples [ 7 , 11 13 ]. A systematic review of studies conducted in Iran showed that the vast majority of breast milk samples contained lead levels above the World Health Organization’s recommended level (< 5 μg/L) [ 13 ]. In Palestine, about one in five breast milk samples collected in the time period between May and April 2015 contained lead above the World Health Organization’s recommended level [ 7 ].…”
Section: Introductionmentioning
confidence: 99%